These Are the Ones - Dalrymple, Rob (Biblica, 2005)
The thematic features relating to John’s depiction of the righteous in the intercalations of Rev 11,3-13 and 7,1-17 as well as how these features might affect our understanding of Revelation 7,1-17 are examined. Four foci pertaining to the righteous are explicitly present in the account of the Two Witnesses (11,3- 13). All four foci, also, materialize in the description of the 144,000 (7,1-8) and the Great Multitude (7,9-17). However, when we examine Rev 7,1-8, we find that John only incorporates the first two of the four foci (Divine Protection and Witnesses) while in the account of 7,9-17, only the latter two appear (Enduring Persecution and Vindication of the Righteous). If, however, we read Rev 7,1-17 as the account of one group, then the thematic parallels with the intercalation of Rev 11,3-13 are retained.